Photoprocesses in bis(18-crown-6)-1,3-distyrylbenzene and its complexes with metal perchlorates - Atabekyan, Levon S.; Freidzon, Alexandra Ya; Chibisov, Alexander K.; Gromov, Sergey P.; Vatsadze, Sergey Z.; Nuriev, Vyacheslav N.; Medvedko, Alexey V. (Dyes and pigments, 2021)
Photoprocesses of bis(18-crown-6)-1,3-distyrylbenzene (DSB) and its complexes with barium and lead perchlorates in a MeCN–CH2Cl2 (9:1, v/v) mixture were studied by absorption, luminescence, and laser kinetic spectroscopies. Unlike its strongly conjugated 1,4-isomer, 1,3-derivative shows almost independent behavior of its chromophoric subunits and is capable of phototransformations not observed in 1,4-distyrylbenzenes. Triplet DSB complexes are involved in the radiationless deactivation of the excited state along with the fluorescence processes. The most effective intersystem crossing was observed for the complex with lead perchlorate. The process is accompanied by a drastic decrease in the quantum yield of DSB fluorescence. Quantum chemistry (DFT and TDDFT) is used to calculate the geometric structure and absorption spectra of DSB and its complexes with barium and lead cations and to explain the observed results. •The nano- and microsecond kinetics of bis(18-crown-6)-1,3-distyrylbenzene and its complexes with Ba2+ and Pb2+ is studied.•1,3-Distyrylbenzenes show independent behavior of their chromophoric subunits and are capable of novel phototransformations.•Quantum chemistry explains the experimental data. The results are useful for the rational design of photoswitches and sensors.